Mystery Writers of America presents Vengeance - Child, Lee (Corvus, 2012)
Features new stories in which characters take the law into their own hands in search of vengeance, with contributions by Lee Child, Michael Connelly, Dennis Lehane, and Karin Slaughter as well as up-and-coming new writers in the field.